1971
DOI: 10.1111/j.1432-1033.1971.tb19657.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of Threonine Dehydratase from Yeast

Abstract: Biosynthetic L‐threonine dehydratase was purified from bakers' yeast and crystallized. The enzyme was homogeneous as judged by ultracentrifugation and electrophoresis. s20, was 9.2 S, and the molecular weight was estimated to be approximately 185000. The enzyme exhibits a slight yellow color. An absorption maximum in the visible region was at 410 nm. Apparent Michaelis constants for L‐threonine and L‐serine are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This would be a prerequisite for the catabolism of threonine via 2-oxobutyrate by the bacterium. The properties of the dehydratase from the Corynebacterium were similar to those of the enzyme in Rhodopseudomonas spheroides (Datta, 1966;Barritt, 1971), a yeast (Katsunuma et al, 1971) and a species of Brevibacterium (Miyajima & Shiio, 1972) rather than in the enteric bacteria. In the latter case, valine only normalizes the substrate-response curve in the presence of isoleucine (Umbarger, 1973).…”
Section: Discussionmentioning
confidence: 67%
“…This would be a prerequisite for the catabolism of threonine via 2-oxobutyrate by the bacterium. The properties of the dehydratase from the Corynebacterium were similar to those of the enzyme in Rhodopseudomonas spheroides (Datta, 1966;Barritt, 1971), a yeast (Katsunuma et al, 1971) and a species of Brevibacterium (Miyajima & Shiio, 1972) rather than in the enteric bacteria. In the latter case, valine only normalizes the substrate-response curve in the presence of isoleucine (Umbarger, 1973).…”
Section: Discussionmentioning
confidence: 67%
“…Our results demonstrated that phosphate changes both the ligand binding and the temperature effects including temperature op- timum, activation energy, and thermal stability. The enzyme from C. malfosa is activated by valine, inhibited by isoleucine, and a sigmoid substrate saturation curve is obtained in the absence of isoleucine, comparable to the enzyme from S. cerevisiae [3,11]. In the presence of phosphate, the K, for threonine, the Ki for isoleucine, and the K, for valine increase, while the co-operativity between substrate molecules and the C. maltosa enzyme decreases.…”
Section: Cphosphatel (M)mentioning
confidence: 79%
“…It was reported that the L Ile concentrations measured in the cells of C. glutamicum were always higher than the extracellu lar ones at all fermentation process [16], so the TDH of the strains was exposed in a high concentration of L Ile. A comparison of amino acid sequences between the tdcB polypeptide and the biosynthetic TDH of yeast (encoded by ILV1) and E. coli (encoded by ilvA) and other strains revealed various extents of homology [17][18][19]. The surprising difference from those homol ogies is in the carboxy terminal region [14,20], and analysis of the structure of TDH by site directed mutation in this site may be a strategy for further increasing L Ile production.…”
Section: Discussionmentioning
confidence: 99%